Social Resilience of Minority Group: Study on Syiah Refugees in Sidoarjo and Ahmadiyah Refugees in Mataram - Cahyo Pamungkas (Universitas Islam Negeri Mataram, 2015)
This research conceptually aims to find out the strategy the Shia community in Sidoarjo, East Java, and Ahmadiyya community in Mataram, West Nusa Tenggara, have employed to defend themselves from the pressure of the state and Sunni Muslim as majority group due to the differences in textual interpretation toward Islamic Holy Scriptures (The Qur’an). The theoretical implication from this study is to evaluate and criticize social resilience concept which refers to developmentalistic perspectives such as the use of social capital. In this article, social resilience is closely related to strategy of minorities to establish a tolerant multi religious community. This study argues that social resilience of religious minority groups, i.e. Shia in Sidoarjo and Ahmadiyya in Mataram, is formed by various aspects, such as the government policies on religious life, history of group formation, social relations and network, understanding towards religious values and spirituality, and cultural bonds in the community. DOI: http://dx.doi.org/10.20414/ujis.v19i2.418